Developing Google Sites and Mathigon Learning Media to Support Stu-dents’ Conceptual Understanding in Solving Linear Equations in One Variable - Agustin, Dhea Puspita Putri; Apriani, Maria Suci; Sali, Melania Liliastri (UNNES JOURNAL, 2024)
This research notes that there is still a lack of focus on implementing digital-based learning media to helo students in understanding of the concept of Linear Equations with One Variable and in finding the solution in one of the East Nusa Tenggara (NTT) State Middle Schools. Virtual balance models can be used to help students learn the concept of linear equations. Therefore, this study aims to develop digital-based learning media, considering the quality criteria of being valid, practical, and effective. The research adopts the Research and Development (R&D) methodology with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects are six seventh-grade students from one of the State Junior High Schools in East Nusa Tenggara with high, moderate, and low cognitive abilities. Data on the quality of learning media are obtained through questionnaires, interviews, and learning outcome tests. The learning media is categorized as highly valid with a percentage of 88% and highly practical with a percentage of 94%. Additionally, the learning media is deemed effective, with over 80% of the research subjects scoring above the Minimum Completion Criteria (KKM). Digital-based learning media utilizing the balance model feature in Mathigon with the help of Google Sites, was developed to facilitate students' understanding of concepts at one of the State Middle Schools in NTT. The problems presented in the media carry the culture that exists in the NTT region. Thus, students can easily imagine these problems because they are close to their lives. Both teachers and students feel assisted by the developed learning media. Using this media, teachers enable to monitor the students' progress and students also can participate actively during this learning. Penelitian ini mencatat bahwa masih kurangnya fokus pada implementasi media pembelajaran berbasis digital untuk membantu siswa dalam memahami konsep Persamaan Linear Satu Variabel (PLSV) dan penyelesaiannya di salah satu SMP Negeri Nusa Tenggara Timur (NTT). Model keseimbangan virtual dapat dimanfaatkan untuk membantu siswa dalam mempelajari konsep persamaan linear. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis digital pada materi persamaan linear satu variabel dengan memperhatkan kualitas yaitu valid, praktis dan efektif. Penelitian ini menggunakan jenis penelitian dan pengembangan atau Research and Development (R&D) dengan model ADDIE (Analyze, Design, Development, Implementation, Evaluation). Subjek penelitian adalah enam peserta didik kelas VII di salah satu SMP Negeri Nusa Tenggara Timur dengan kemampuan kognitif tinggi, sedang dan rendah. Data kualitas media pembelajaran diperoleh dari kuesioner, wawancara dan tes hasil belajar. Media pembelajaran dikategorikan sangat valid dengan persentase 88% dan sangat praktis dengan persentase 94%. Serta media pembelajaran juga dikatakan efektif, lebih dari 80% subjek penelitian mendapatkan nilai diatas Kriteria Ketuntasan Minimal (KKM). Media pembelajaran berbasis digital dengan memanfaatkan fitur model keseimbangan pada Mathigon berbantu Google Sites, dikembangkan untuk memfasilitasi pemahaman konsep siswa di salah satu SMP Negeri di NTT. Permasalahan yang disajikan dalam media tersebut, mengusung budaya yang ada pada daerah NTT. Sehingga siswa dapat dengan mudah membayangkan permasalahan tersebut karena dekat dengan kehidupan mereka. Guru dan peserta didik merasa terbantu dengan media pembelajaran yang telah dikembangkan. Guru dapat memonitoring perkembangan siswa dan siswa melalui media ini dapat terlibat aktif dalam pembelajaran.